Effects of Bone Marrow-derived Mesenchymal Stem Cells-loaded Self-assembling Peptide Scaffold on Synovial Volume and Cartilage Thickness on Rabbit Model of Rheumatoid Arthritis - Rina Sha; Jizheng Li (Journal of Animal and Plant Sciences, 2025)
This study was to assess the potential therapeutic effects of bone marrow-derived mesenchymal stem cells (BMSCs) loaded onto self-assembling peptide scaffolds on the rabbit model of rheumatoid arthritis (RA). The morphology of prepared BMSCs self-assembling peptide scaffold with the capability for loading was observed andcell biocompatibility was assessed. A total of sixty New Zealand white rabbits were utilized to establish RA model and were randomly rolled into Control group, Bracket group, BMSCs group and Negative group. In Control group, the joint was exposed surgically (joint exposure procedure) but was not subjected to any therapeutic intervention, while in Bracket group, the peptide scaffold was placed into the joint. In BMSCs group, BMSCs-loaded peptide scaffolds were implanted into the joints. The Negative group received no treatment, undergoing neither surgical procedures nor any therapeutic intervention, maintaining the normal physiological state.The extent of joint swelling was measured and assessed in rabbits. MRI scans of the rabbit knee joints were performed to evaluate the status of the synovium and cartilage. Hematoxylin-Eosin (HE) was performed on rabbit joint cartilage tissues to assess the post-treatment cartilage tissue status. ELISA was utilized for measurement ofinflammatory factor levelsin the rabbits. Western blotting was conducted to assess key protein expressions. The peptide hydrogel showed excellent biocompatibility. MRI evaluation showed that the volume of synovial hyperplasia in BMSCs group was significantly lower than that in Control group and Bracket group (P<0.05), and cartilage thickness increased significantly over time, reaching 0.91 ± 0.07 mm at 3 months (P<0.05). ELISA analysis indicated that the levels of inflammatory cytokines (tumor necrosis factor(TNF)-α, interleukin(IL)-1β, IL-6, C-reactive protein(CRP)) in BMSCs group were significantly lower than those in Control group and Bracket group (P<0.05). Western blotting results demonstrated that the expression of COL2A1 protein was increased in BMSCs group (0.89 ± 0.09 vs.Control group 0.44 ± 0.07, P<0.05), while the expression of cartilage oligomeric matrix protein(COMP) was significantly decreased (0.89 ± 0.11 vs.Control group 0.64 ± 0.08, P<0.05). HE staining revealed that after 3 months of BMSCs treatment, cartilage thickness increased, chondrocyte proliferation was significant, matrix staining was well-preserved, and no vascularity was observed. Both synovial pathology scores and Mankin scores for cartilage indicated that the pathological damage in BMSCs group was significantly improved (P<0.05), with better outcomes compared to Bracketgroup.BMSCs-loaded self-assembling peptide scaffold has potential therapeutic effects on rabbit model of RA, especially in terms of reducing synovial overgrowth and promoting cartilage repair.
Keywords: rheumatoid arthritis; bone marrow-derived mesenchymal stem cells; self-assembling peptide scaffolds; MRI; rabbit model